Kedudukan Dan Perlindungan Anak Luar Kawin Dalam Perspektif Hukum Di Indonesia - Emilda Kuspraningrum (Jurnal Risalah Hukum, 2006)
The status of extra marital children can be seen in Kitab Undang – Undang Hukum Perdata and Undang – Undang Nomor 1 Tahun 1974 tentang Perkawinan. The status of extra marital children is only considered having legal and familial relationship, with all the consequences, with the mother or the woman giving birth to the child. This also happens concerning the matters pertaining to inheritance. Extra marital children can obtain the legal status only if their biological or surrogate fathers acknowledge them legally through a formal certificate. Key words : anak (children) orang tua (parents) pengakuan anak luar kawin (acknowledgement of an extra marital child)